Information asymmetries in intrafamily business succession - Sven Wolff; Sabrina Schell; Petra Moog (BRQ Business Research Quarterly, 2022)
The often long-lasting process of intrafamily business succession involves contracts for management and ownership transfer that unfold in a complex series of stages. The older and larger a family business, the more heterogeneous the involved family members' interactions and interests can become. These differences become obvious in the succession process. Also, in entrepreneurial families, information is not easy to obtain and is neither perfect nor unlimited, for example, with regard to expectations regarding the duration or the type of business succession. Information asymmetries can arise. This article investigates the drivers of information asymmetries and provides insight into the current research by investigating information asymmetries and their impact during different phases of intrafamily business succession. Data from 215 German firms reveal the occurrence of specific information asymmetries during different phases of intrafamily business succession.
Keywords: M1; M59; D82; L2; 650; Business succession; information asymmetries; family firms; succession process